Environmental and developmental determinants of obesity in Cebu, Philippines - Dahly, Darren L. (Ann Arbor Michigan ProQuest LLC, 2009)
Obesity is now recognized as a serious challenge to global public health. Obesity is often viewed as a problem that results from a deficiency in a person's character; that obesity is the consequence of gluttony and sloth. However, obesity is impacted by a variety of factors that are largely exogenous to human choices. We investigated both how shared environment and individual level socio-economic status influence obesity risk, as well as how prenatal characteristics can increase human susceptibility to the obesogenic effects of modern environments before we are even born. Analyses were conducted using data from the Cebu Longitudinal Health and Nutrition Survey, a community based study of a one year birth cohort (1983) followed up until young adulthood (2005). Using the spatial scan statistic we found that measures of overweight and obesity were spatially clustered in the study area Metro Cebu. The locations of these clusters coincided with the urban core of Cebu, but also extended into peri-urban and rural areas as well. Clustering in the males was largely explained by the spatial distribution of individual level socio-economic status. We then used multivariable linear models to explore the joint impact of community level urbanicity and multiple indicators of individual level socio-economic status on multiple measures of overweight and obesity. We found that socioeconomic status was positively associated with obesity in males but not females. Lastly, we tested the mismatch hypothesis, which generally posits that maternal constraint of fetal growth can lead to developmental changes in utero that increase an individual's susceptibility to obesogenic environments. More specifically, we found that that the positive association between socio-economic status and central adiposity in male study participants was amplified in firstborns.--Abstract.
Thesis (Ph.D.)--University of Carolina, Chapel Hill, 2009.
Keywords: Obesity -- Cebu City, Philippines